British Kings & Queens : From the Anglo-Saxons to the House of Winsor - Forty, Sandra (London Compendium, 2009)
This book tells the story of over a thousand years of British history through the lives of its great monarchs.
Include Index and Color Illustration
Keywords: Great Britain -- Kings and rulers